RESPON PEMBERIAN PUPUK ORGANIK CAIR (POC) HERBAFARM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAYAM CABUT (Amaranthus tricolor L.) - Yudi Triyanto (JURNAL AGROPLASMA, 2019)
The design used a random Design Group (RAK) factorial with 1 factors and five levels of treatment: O0:0 cc/l, O1:5 cc/l, O2:10 cc/l, O3:15 cc/l, O4:8 cc/l, and continued with the test Duncan's Multiple Range tests. The parameters observed were higher plants (cm), number of leaves (strands), diameter clump (cm) and weight of fresh plant (gr). From the results of this research conclusion, delivery of Liquid organic fertilizer (POC) Herbafarm the real effect against all the observed parameters such as: plant height (cm), number of leaves (strands), diameter clump (cm) and weight of fresh plant (gr). Keywords: Herbafarm, growth, spinach Unplug (Amaranthus tricolor L.)